Effect of Salinities and Dietary Patterns toward Fullness of Gut and Gut Evacuation Time of the Newly Introduced Penaeus merguiensis Larvae - Mostafa Imhmed Ighwerb; Johannes Hutabarat; Ervia Yudiati; Rudhi Pribadi; Widianignsih Widianingsih; Retno Hartati; Abidin Nur II; Arumning T. Fauziah; Jelita Rahma Hidayati (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
The gut capacity of shrimp larvae is minimal, and their digestion is often challenged by the inevitable fact that they tend to develop slowly during the zoea stage. Many studies approved that the digestive capacity of shrimp larvae could be improved by increasing the retention time of food in the intestine. Gut evacuation time and fullness of the gut are crucial parameters in assessing the growth of shrimp larvae, and the diet as well as  environmental conditions indeed influence the activity of these parameters. Although many species of shrimps have a wide salinity tolerance, more specific research on salinity and its relation to the type of diet is necessary to find the optimum condition supporting the growth of shrimp larvae. By employing Penaeus merguiensis larvae, this study evaluates the effect of three nominal salinities (28, 32, and 36 ppt) and types of diets (Diet A: 100% live feed; Diet B: 100% FRIPPAK; Diet C: a combination of Diet A and Diet C, 50 % each) toward the fullness of gut and gut evacuation time of the newly introduced Penaeus merguiensis larvae culture. The result showed that the longest gut evacuation time and the highest percentage of gut's fullness were found in all Zoea reared with Diet A at salinity 28 and 32 ppt; Zoea-1 at 28 ppt with Diet A; Zoea-2 at 32 ppt with Diet A; Zoea-3 at 32 ppt with Diet A. Longer gut evacuation time would have an impact on the higher percentage of the fullness of gut. The higher fullness of the gut also indicates that the larvae have the best capacity to produce energy and achieve optimum growth.